2016
DOI: 10.1515/raon-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis estimation under the light of metabolic tumor parameters on initial FDG-PET/CT in patients with primary extranodal lymphoma

Abstract: BackgroundNon-Hodgkin’s lymphomas arising from the tissues other than primary lymphatic organs are named primary extranodal lymphoma. Most of the studies evaluated metabolic tumor parameters in different organs and histopathologic variants of this disease generally for treatment response. We aimed to evaluate the prognostic value of metabolic tumor parameters derived from initial FDG-PET/CT in patients with a medley of primary extranodal lymphoma in this study.Patients and methodsThere were 67 patients with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Okuyucu et al. demonstrated that SUV mean was a potential risk factor for OS in primary extranodal lymphoma ( 36 ). Instead, in our research, SUV max and SUV mean showed no significance with PFS or OS in MCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Okuyucu et al. demonstrated that SUV mean was a potential risk factor for OS in primary extranodal lymphoma ( 36 ). Instead, in our research, SUV max and SUV mean showed no significance with PFS or OS in MCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to recently published data, it remains controversial whether MTV and TLG can be used as prognosticators . Sharma et al .…”
Section: Discussionmentioning
confidence: 99%
“…have found that a high level of TLG is the only significant predictive factor for relapse‐free survival. Okuyucu et al . have found that SUV mean , MTV and TLG are potential risk factors for outcomes in patients with primary extranodal lymphoma (DLBCL, MALT, Burkitt and mantle cell lymphoma).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Оказалось, что высокий уровень TLG связан с беспрогрессивной выживаемостью (р = 0,02); уровень MTV имеет выраженную тенденцию к этому (р = 0,06). Okuyucu K. et al [37] у 67 больных экстранодальными неходжкинскими лимфомами показали, что высокие базовые показатели MTV и TLG являются потенциальными факторами риска ухудшения как общей, так и безрецидивной выживаемости. Кроме того, имела значение и локализация опухоли: при поражении яичек и ЦНС риск рецидива был выше.…”
Section: другие виды неходжкинских лимфом другие виды неходжкинских лимфомunclassified